Radiographic evaluation of pulmonary tuberculosis: A comparative study of pre- and post-treatment chest X-rays at Royal Prima Hospital - Rahmi, Clairine Altin Nur; Pulungan, Ica Yulianti; Nasution, Ikhwanul Hakim; Thelim, Adeline (Buletin Kedokteran & Kesehatan Prima, 2024)
Pulmonary tuberculosis (TB) is a significant global health concern. Chest radiography is an essential tool for the diagnosis and monitoring of TB treatment. This retrospective cohort study aimed to analyze changes in chest radiographic findings among TB patients before and after treatment at Royal Prima Hospital. The study included 30 patients with TB who underwent repeated chest radiography between May 2023 and May 2024. Patient data were collected from the medical records. Descriptive analysis and the chi-square test were used to compare changes in radiographic findings between the treatment and non-treatment groups. Of the 30 patients, 15 (50%) showed positive changes on post-treatment radiographs, while the remaining 15 (50%) did not. The Chi-Square test revealed a significant difference (P < 0.05) between the two groups. Patients who received treatment had four-fold higher odds of experiencing radiographic changes than those who did not. These findings align with those of previous research demonstrating the efficacy of TB treatment in the repair of lung damage. Positive changes in post-treatment radiographs indicated that the treatment effectively suppressed Mycobacterium tuberculosis growth and facilitated lung tissue repair. Pulmonary TB treatment exerts a significant impact on changes in chest radiographic findings. This study underscores the importance of adequate TB treatment to achieve cure and prevent complications.